My mother's money : a guide to financial caregiving - Pinsker, Beth (Crown Currency, 2025)
"A comprehensive, compassionate guide for navigating end-of-life financial decisions for an aging parent or other loved one-from an award-winning journalist who is also a Certified Financial Planner"-- Provided by publisher.